Pengaruh Cyberbullying terhadap Self-Blaming pada Remaja Pengguna Instagram - Putri, Cindy Hapsari Maharani Pujiantoro; Suwarni, Eny; Roebianto, Adiyo (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
Technological developments make it easier for humans to network widely through social media such as Instagram. Active Instagram users in Indonesia are dominated by teenagers. The existence of social media allows cyberbullying to occur, which is an act of bullying via the internet that can trigger victims to blame themselves. The purpose of this study was to determine the effect of cyberbullying on adolescents who experience self-blaming via Instagram. The method used in this study is quantitative with a non-experimental regression approach. The data collection technique was carried out using an instrument in the form of a Likert scale, while the data collection method was through a questionnaire filled out via the Google form. Participants in this study were young Instagram users aged 18-22 years. Based on the results of the simple regression test that has been carried out by researchers, it can be concluded that cyberbullying has a significant effect on self-blaming. After conducting this research, it is hoped that further researchers can intervene through education on social media such as distributing e-flyers related to cyberbullying behavior so that they can suppress cyberbullying actions that occur on social media.